2020
DOI: 10.3390/ijerph17072533
|View full text |Cite
|
Sign up to set email alerts
|

Distress Due to Urinary Problems and Psychosocial Correlates among Retired Men in Hong Kong

Abstract: Urinary problems are common among aging men, but there is a paucity of research efforts to understand the psychosocial aspects of the illness. This study aims to understand how common and distressing urinary problems are for newly retired men in Hong Kong and to test the associations between mental health, self-stigma of seeking help, fatigue, self-efficacy, self-esteem, and distress due to urinary problems. To assess this, 139 out of 200 members of a retired men’s social club (mean age 63.5) were successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Previous studies also indicated that the incidence of psychosocial complications was associated with urinary incontinence. Accordingly, older people with urinary incontinence had a weaker psychosocial health status ( Chiu et al, 2020 ; Omu et al, 2020 ; Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also indicated that the incidence of psychosocial complications was associated with urinary incontinence. Accordingly, older people with urinary incontinence had a weaker psychosocial health status ( Chiu et al, 2020 ; Omu et al, 2020 ; Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This attitude is frequently detected amongst Asian women, specifically South Asian ones, and affects discussions about the disease and reception of the related care services. On the other hand, concealing the inconveniences associated with the disease due to being shameful exerts a negative impact on patients’ mental health ( Higa et al, 2008 ; Chiu et al, 2020 ). Furthermore, since urine is considered dirty in the Islamic culture and urinary incontinence is regarded as uncleanliness, older adults’ women with this disease have a constant fear from the way others may treat them.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the high levels of stress and embarrassment that UI causes, due to the smell and discomfort resulting from the loss of urine (12) . For these reasons, some women change their lifestyle, for example: reducing sexual contact, increasing their spending on medication, and renouncing their social life, impacting on the quality of social and professional life of these women (12,13) , having great impact on their psychological health (13) .…”
Section: Introductionmentioning
confidence: 99%
“…The local age-specific prevalence in adult males was only reported at selected older age groups, such as 64% for age 51-60 and 81% for age >70, for having ≥1 void per night [21]. Furthermore, in a small-scale local interview study, 60% of newly retired men had reported that their sleep was disturbed by nocturia in the past six months, and more than half of them had not taken any actions for solving this problem but felt distressed [22]. Yet, the previous prevalence studies were mainly focused on older populations of selected age groups either from clinical settings or through phone interviews [20,21].…”
Section: Introductionmentioning
confidence: 99%